2017
DOI: 10.1038/s41598-017-07114-x
|View full text |Cite
|
Sign up to set email alerts
|

Chickpea-Fusarium oxysporum interaction transcriptome reveals differential modulation of plant defense strategies

Abstract: Fusarium wilt is one of the major biotic stresses reducing chickpea productivity. The use of wilt-resistant cultivars is the most appropriate means to combat the disease and secure productivity. As a step towards understanding the molecular basis of wilt resistance in chickpea, we investigated the transcriptomes of wilt-susceptible and wilt-resistant cultivars under both Fusarium oxysporum f.sp. ciceri (Foc) challenged and unchallenged conditions. Transcriptome profiling using LongSAGE provided a valuable insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…A comparison of the different studies that analyzed changes in plant transcriptomes, proteomes and metabolomes in response to FW infection reinforces the role of chitinases, PR proteins, ROS activating enzymes, phenolic compounds, flavonoids, phytoalexins in imparting wilt resistance (Castillejo et al, 2015;Kumar et al, 2016;Upasani et al, 2017;Bani et al, 2018a,b). These studies also highlight the significance of molecules that participate in cellular metabolism including carbohydrate, protein, nucleotides (Castillejo et al, 2015;Xue et al, 2015;Kumar et al, 2016) and signaling pathways involving MAP kinase, serine threonine kinase and various phytohormones (Gupta et al, 2013a,b;Xue et al, 2015).…”
Section: Proteomics and Metabolomics To Elucidate Plant Defense Mechamentioning
confidence: 63%
See 1 more Smart Citation
“…A comparison of the different studies that analyzed changes in plant transcriptomes, proteomes and metabolomes in response to FW infection reinforces the role of chitinases, PR proteins, ROS activating enzymes, phenolic compounds, flavonoids, phytoalexins in imparting wilt resistance (Castillejo et al, 2015;Kumar et al, 2016;Upasani et al, 2017;Bani et al, 2018a,b). These studies also highlight the significance of molecules that participate in cellular metabolism including carbohydrate, protein, nucleotides (Castillejo et al, 2015;Xue et al, 2015;Kumar et al, 2016) and signaling pathways involving MAP kinase, serine threonine kinase and various phytohormones (Gupta et al, 2013a,b;Xue et al, 2015).…”
Section: Proteomics and Metabolomics To Elucidate Plant Defense Mechamentioning
confidence: 63%
“…), significantly participating in the defense signaling against FW in chickpea (Gupta et al, 2013a). Similarly, differential expression was obtained by transcriptome profiling of chickpea genotypes JG 62 (Foc susceptible) and Digvijay (Foc resistant) for genes that are involved in lignification, hormonal homeostasis, plant defense signaling, reactive oxygen species (ROS) homeostasis, R-gene mediated defense in response to host-pathogen interaction (Upasani et al, 2017). An integrated analysis of transcriptome and metabolome data from the root samples of control and FOP infected seedlings in common bean demonstrated that pathogen establishment occurs after 24 h of infection, which is accompanied by timely induction of the defense mechanism.…”
Section: Functional "Omics" Studies To Delineate Host Genes Impartingmentioning
confidence: 99%
“…Further, race-dependent defense responses were observed (Gurjar et al, 2012). A similar study with resistant and susceptible interactions with Foc race 1, 2, and 4 was conducted recently with the LongSAGE method (Upasani et al, 2017). Clustering analysis and interaction networks of differentially expressed genes (DEGs) identified that the resistant interaction is characterized by ROS production, SA production, lignification, R -gene expression, and hormone homeostasis.…”
Section: Using Genomics To Understand the Basics Of Plant–pathogen Inmentioning
confidence: 99%
“…In the case of chickpea, several transcriptome studies have been undertaken to identify key abiotic stress-responsive genes for tolerance to drought and salinity (Garg et al, 2016;Mashaki et al, 2018). In contrast, for identification of biotic stress-responsive genes in chickpea, a few studies have been reported (Jain et al, 2015;Upasani et al, 2017). In case of AB stress mechanism, a few gene expression studies have been performed, mainly using 768features expression arrays (Coram and Pang, 2006;Mantri et al, 2010), however, a genome-wide and comprehensive analysis of genes involved in AB resistance is not yet available.…”
Section: Introductionmentioning
confidence: 99%